Comprehensive Understanding of the HZO-based n/pFeFET Operation and Device Performance Enhancement Strategy - Kuk, Song-hyeon; Han, Seung-min; Kim, Bong-ho; Baek, Seung-Hyub; Han, Jae-hoon; Kim, Sang-hyeon (2021 IEEE INTERNATIONAL ELECTRON DEVICES MEETING (IEDM), 2021)
We report a comprehensive understanding of HZO based n/pFeFET operation using (double-pulsed) quasi-static CV and pulsed IV techniques, providing the true nonvolatile polarization and excess trap density, which has not been reported yet. Also, we conceived new insight into the trapped charge and polarization switching by the method, based on the asymmetry of electron/hole trapping in n/pFeFET. Through the analysis, we propose a new erasing operation, resulting in enhanced performance (ex. endurance > 10(10) cycles), and also proposed physical models of the n/pFeFET operation.